2022
DOI: 10.3389/fimmu.2022.973089
|View full text |Cite
|
Sign up to set email alerts
|

Role of released mitochondrial DNA in acute lung injury

Abstract: Acute lung injury(ALI)/acute respiratory distress syndrome(ARDS) is a form of acute-onset hypoxemic respiratory failure characterised by an acute, diffuse, inflammatory lung injury, and increased alveolar-capillary permeability, which is caused by a variety of pulmonary or nonpulmonary insults. Recently, aberrant mitochondria and mitochondrial DNA(mtDNA) level are associated with the development of ALI/ARDS, and plasma mtDNA level shows the potential to be a promising biomarker for clinical diagnosis and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 202 publications
0
10
0
Order By: Relevance
“…Many lines of MDVs research have shown greater MDVs level in mild stress conditions than mitophagy, which is the canonical machinery for removing the damaged mitochondria [ 1 , 8 11 ]. Recently, selective cargos of mitochondrial oxidized molecules, such as mitochondrial DNA (mtDNA), peptides, proteins and lipids, to be degraded by lysosomes have been shown [ 3 , 12 , 13 ]. Moreover, immune regulation by MDVs has been emphasized in several reports of inflammation-associated diseases [ 3 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many lines of MDVs research have shown greater MDVs level in mild stress conditions than mitophagy, which is the canonical machinery for removing the damaged mitochondria [ 1 , 8 11 ]. Recently, selective cargos of mitochondrial oxidized molecules, such as mitochondrial DNA (mtDNA), peptides, proteins and lipids, to be degraded by lysosomes have been shown [ 3 , 12 , 13 ]. Moreover, immune regulation by MDVs has been emphasized in several reports of inflammation-associated diseases [ 3 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, selective cargos of mitochondrial oxidized molecules, such as mitochondrial DNA (mtDNA), peptides, proteins and lipids, to be degraded by lysosomes have been shown [ 3 , 12 , 13 ]. Moreover, immune regulation by MDVs has been emphasized in several reports of inflammation-associated diseases [ 3 , 12 , 14 ]. As such, MDVs have gained a wide interest in many mitochondria-associated disorders/diseases, such as cancers [ 15 , 16 ], aging [ 17 19 ], cardiovascular diseases [ 20 , 21 ], and neurodegenerative disorders [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that mtDNA can trigger inflammatory cytokine production and aggravate lung fibrosis through TLR9 signaling and noncanonical cGAS-STING signaling [51]. In thoracic transverse aortic constriction induced cardiomyopathy, mtDNA is capable of inducing dilated cardiomyopathy through TLR9 signaling [22].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the release of mtDNA during COVID-19 has been investigated significantly less, even though it is related to NETs and immunothrombosis. Therefore, the present study aimed to quantify mtDNA [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%